A novel passivating contact approach for enhanced performance of crystalline silicon solar cells. (1st March 2023) - Khokhar, Muhammad Quddamah; Hussain, Shahzada Qamar; Kim, Youngkuk; Dhungel, Suresh Kumar; Yi, Junsin
Abstract: Passivated contacts based on ultrathin silicon oxide (SiOx ) layers and phosphorus-doped nanocrystalline silicon oxide (nc-SiOx (n)) layers have been examined for their application in tunnel oxide-passivated contact (TOPCon) solar cells. Passivated contact nc-SiOx (n)/SiOx, is accomplished by implementing a thermally grown SiOx tunnel layer and a plasma-enhanced chemical vapor deposited (PECVD)-grown nc-SiOx (n) layer, which are subsequently transformed into a more crystalline phase by annealing at a higher temperature. In this research, a 3.2 × 3.2 cm solar cell was fabricated, where the base material was n-type crystalline silicon (c-Si(n)), and an aluminum oxide (Al2 O3 ) acts as a passivation layer which helps to enhanced the passivation properties and indium tin oxide (ITO) layer was used on the front side, which could serve as an anti-reflection coating (ARC), respectively. The influence of the temperature, doping level, and thickness of nc-SiOx (n) on the surface passivation of the contacts was investigated. Superior recombination current density (Jo ) values of up to 2.9 fA/cm 2 were assessed for the nc-SiOx (n)/SiOx contacts. TOPCon solar cells with top boron-doped emitter, Al2 O3, and ITO/rear stack of nc-SiOx (n)/SiOx passivation contacts were formed and resulted in Voc  = 650 mV and FF = 78%. Furthermore, we focused on ameliorating the achievements of solar cells using a transparent passivating contact-based nc-SiOx (n), as well as the passivation process and operating principle. Graphical abstract: Image 1 Highlights: Innovative passivation contact using nc-SiOx (n)/SiOx /c-Si contact. Stack of Al2 O3 /ITO front contact draw a maximum amount of current. Excellent passivation quality achieved with iVoc of 733 mV and Jo of 2.9 fA/cm 2 .